Pelatihan Public Speaking dengan Metode CCP bagi Siswa Siswi UPT SMAN 13 Maros - Izki Fikriani Amir; Muhammad Idris (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
High school students are the young generation who have the potential and have the opportunity to play an active role in the development of the nation and the nation. To support their ability to compete in today's era, high school students are required to have self-confidence, be able to communicate politely, and be polite as part of public speaking. If you do not have the ability to communicate in public appropriately due to a lack of self-confidence, then the interaction cannot run smoothly. Therefore, to provide understanding, public speaking training is held using the CCP (Confident, Content and Performance) method. This dedication activity was a collaboration between the lecturer who held the tridharma activities of higher education and the UPTD SMAN 13 Maros which is located in Pucak Village. By using the practice method which begins with increasing self-confidence, followed by creating content and finally preparing for a live performance. the enthusiasm of the participants was very high, various questions were asked during the discussion so that this activity could provide training in the development of public speaking presentation skills